Cost–effectiveness of bronchial thermoplasty in commercially-insured patients with poorly controlled, severe, persistent asthma. (April 2015) - Cangelosi, Michael J; Ortendahl, Jesse D; Meckley, Lisa M; Bentley, Tanya GK; Anene, Ayanna M; Shriner, Kelly M; Fox, John
<x xml:space="preserve">Abstract</x> Objectives: We examined the cost–effectiveness of treating poorly controlled, severe, persistent asthma patients with bronchial thermoplasty (BT), a novel technology that uses thermal energy to reduce airway smooth muscle mass, with 5-year outcome data demonstrating a durable reduction in asthma exacerbations. Study design: We conducted a model-based cost–effectiveness analysis assessing 5-year healthcare utilization, patient quality of life and adverse events. Methods: We utilized Markov modeling to estimate the costs and quality-of-life impact of BT compared with high-dose combination therapy among poorly controlled, severe, persistent asthma patients: those requiring high-dose combination therapy and having experienced an asthma exacerbation-related ER visit in the past year. Results: The cost–effectiveness of BT was US$5495 per quality-adjusted life year; and approximately 22% of sensitivity analysis iterations estimated BT to reduce costs and increase quality of life. Conclusions: BT is a cost–effective treatment option for patients with poorly controlled, severe, persistent asthma.